2021
DOI: 10.1097/ncc.0000000000000986
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Depression and Sleep Quality and Associated Factors in Women Receiving Chemotherapy for Ovarian Cancer

Abstract: Background: Although women with ovarian cancer experience depression and poor sleep quality, little is known about how various factors, particularly self-efficacy, might be associated with these conditions. Objectives: The aim of this study was to examine the prevalence of and changes in depression and sleep quality and the factors associated with these conditions in a cohort of women with ovarian cancer before, during, and after chemotherapy. Methods: A prospective repeated-measures design was adopted in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Previous studies have estimated 24.3% to 80.0% of women with gynecological cancer had poor sleep quality. 10,41 Our study shows that 47.5% report that the subjective sleep quality is poor/very bad, which is at a moderate level. 17.9% of patients in our study report using prescription or over-The-counter sleeping medication at least once in the past month, lower than estimated in other studies of gynecologic cancer patients (36.7%).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies have estimated 24.3% to 80.0% of women with gynecological cancer had poor sleep quality. 10,41 Our study shows that 47.5% report that the subjective sleep quality is poor/very bad, which is at a moderate level. 17.9% of patients in our study report using prescription or over-The-counter sleeping medication at least once in the past month, lower than estimated in other studies of gynecologic cancer patients (36.7%).…”
Section: Discussionmentioning
confidence: 71%
“… 9 And 75.4% to 80.0% of women had poor sleep quality. 10 Insomnia, sleep interruption and drowsiness were the features of sleep disorders, that was, sleep could not meet the needs of the body, causing adverse effects to health outcome. 11 The National Comprehensive Cancer Network (NCCN) recommended that cancer survivors regularly screen for sleep disorders, and advocated behavior therapy instead of drug therapy as the first-line treatment of sleep disorders.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong relationship between depression and symptom distress. A study based on a Chinese ovarian cancer population revealed that more severe of symptom distress predicted higher levels of depressive symptoms ( Wu et al, 2022 ). Similarly, a sample from Korea revealed that ovarian cancer patients experienced more depressive symptoms if they were troubled with more physical symptoms ( Hwang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The occultness of early symptoms, the poor prognosis of the disease in advanced stages, and the fact that about 70% of ovarian cancer diagnoses are made in advanced stages [15] ultimately lead to non-responsiveness to therapeutic strategies and reduced rates of survival to the point where 63% of cases ends in death [15]. In addition to all this, the adverse effects of common treatment methods, such as the invasiveness of surgery and the toxicity of chemotherapy on non-target tissues, which cause infertility [16,17], anemia [18,19], infection [20,21], bleeding [22], insomnia and depression [23][24][25], diarrhea, and constipation [26,27] have led researchers to desire to find an alternative to the standard treatments strongly. The design and development of novel pharmaceuticals with fewer adverse effects and improved antitumoral activity are considered one of the main strategies to confront the previous insufficiencies of ovarian cancer therapeutic approaches [28,29].…”
mentioning
confidence: 99%